Relacje międzypokoleniowe a rodzina - Wrzesień, Witold (Wydawnictwo Naukowe UAM, 2000)
The process of formation of new generations, the creation of generation identity and the generation change, are the phenomena widely analysed in social sciences. This analysis is undertaken both an the global scale and from the perspective of acting inividual. Relations between generations are the resultantof the civilisation changes, which include different spheres of social life: the political system, the economic system, the customs and the moral system of the society. The presented article is an attempt at systematisation of the conceptual model, used to the analysis of the reflections of the global specifics of the generation relations in the family life. We examine such terms and notions as: family, generation, generation change, family socialisation and the generation change, tensions between generations, creation of innovations in the context of generation change, course of the family life and the course of the life of a generation.
Generation relations and the family